Role of Surgery in Saprochaete Capitata (S. Capitata) Sepsis in a Patient with Acute Myeloid Leukemia [Rol de la Cirugía en el Manejo de la Infección Invasora por Saprochaete Capitata] - Alvarez-Zepeda, C (Sociedad Medica de Santiago, 2017)
Saprochaete capitata (S. capitata) fungal sepsis is a severe condition with a clinical presentation that is similar to other yeast originated fungal sepsis. It is observed in patients with hematological malignancies such as acute myeloid leukemia and neutropenia. We report a 23 year old male presenting with cough, fever and malaise. A bone marrow biopsy led to the diagnosis of acute myeloid leukemia. During the first cycle of chemotherapy the patient presented fever: blood cultures were positive for Klebsiella pneumoniae. Despite antimicrobial treatment, fever persisted; a computed tomography showed a focal splenic lesion; a left exudative pleural effusion appeared. A Matrix Assisted Laser Desorption Ionization-Time of Flight mass spectrometry identified the presence of S. capitata. After multiple antifungal treatments and pleural cavity cleansing by means of videothoracoscopy and laparoscopic splenectomy, the infection resolved and the patient completed his chemotherapy. © 2017, Sociedad Medica de Santiago. All rights reserved.
Keywords: Leukemia; Mycoses; Surgical Procedures; Operative